RETRACTED: Efektivitas Pelaksanaan Kebijakan Pengurangan Penggunaan Kantong Plastik Di Kota Sukabumi - Ghifary Prinardi; Dian Purwanti; Yana Fajar Fy Basori (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
Following up on the review of articles published in the Professional Journal carefully, carefully, and considering the article entitled